Interpersonal Relationships in the Transition of Students from Primary to Secondary Schools - Castro Pérez, Marianella (2011)
Interpersonal relationships between students and their parents, teachers and peers during the transition from primary* to secondary school is the topic of this paper. It includes the main results of the survey “Factores de éxito en la transición de sexto grado a sétimo de secundaria” (Success factors on the student’s transition from 6th to 7th grade), held from 2006 to 2007, in the framework of the research program “Perfiles, Dinámicas y Desafíos de la Educación Formal Costarricense” (Challenges of the Costa Rican formal education). One of the objectives in this research project was to obtain the opinion of students from 6th, 7th and 8th grades on what they consider to be key factors for a successful transition between primary and secondary education. The results of this descriptive and exploratory study will contribute to a better understanding of the topic, and will also serve as a starting point for further research in this area. Although quantitative and qualitative techniques are used, the study is non-representative of the national situation. The most important findings reveal that upon entering the secondary school, students have good relationships with their parents, teachers and peers, and their approval and support its fundamental for students to consolidate a position in the new academic group and, of course, to improve their self-perception.